0
$\begingroup$

From An Intermediate Course in Probability by Allan Gut

Suppose that $X\in U(0,1)$. Let $X_{(1)},X_{(2)},\ldots,X_{(n)}$ be the order variables corresponding to a sample of $n$ independent observations of X, and set \begin{equation*} \begin{split} V_{i}=\frac{X_{(i)}}{X_{(i+1)}},\quad i=1,2,\ldots , n-1, \quad \text{and} \quad V_{n}=X_{(n)}. \end{split} \end{equation*} Show that

(a) $V_{1}, V_{2},\ldots,V_{n}$ are independent.

(b) $V_{i}^{i}\in U(0,1)$ for $i=1,2,\ldots,n$.

I am trying to solve (a) by showing that $U$ and $V$ are independent, i.e. that $f_{U}(u)\cdot f_{V}(v)=f_{U,V}(u,v)$.

$U=\frac{X_{k}}{X_{k+1}},\qquad V=\frac{X_{m}}{X_{m+1}}$

\begin{equation*} \begin{split} f_{X_{k},X_{k+1},X_{m},X_{m+1}}(y_{k},y_{k+1},y_{m},y_{m+1})=\int_{-\infty}^{y_{k}}\int_{-\infty}^{y_{k-1}}\cdots \int_{-\infty}^{y_{2}}\int_{y_{k+1}}^{y_{m}}\int_{y_{k+2}}^{y_{m}}\cdots \int_{y_{m+1}}^{\infty}\int_{y_{m+2}}^{\infty}\cdots \int_{y_{n-1}}^{\infty}n!\prod_{i=1}^{n}f(y_{i})\\ \times \, dy_{n}\cdots dy_{m+2}\cdots \, dy_{k+2}\, dy_{1}\cdots dy_{m-1}\cdots \, dy_{k-1}\\ =\int_{-\infty}^{y_{k}}\int_{-\infty}^{y_{k-1}}\cdots \int_{-\infty}^{y_{2}}\int_{y_{k+1}}^{y_{m}}\int_{y_{k+2}}^{y_{m}}\cdots \int_{y_{m+1}}^{\infty}\int_{y_{m+2}}^{\infty}\cdots \int_{y_{n-1}}^{\infty}n!\prod_{i=1}^{n-2}f(y_{i})\Big[F(y_{n})\Big]_{y_{n-1}}^{\infty}\\ \times \, dy_{n-2}\cdots dy_{m+2}\cdots \, dy_{k+2}\, dy_{1}\cdots dy_{m-1}\cdots \, dy_{k-1}\\ = \int_{-\infty}^{y_{k}}\int_{-\infty}^{y_{k-2}}\cdots \int_{-\infty}^{y_{2}}\int_{y_{k+1}}^{y_{m}}\int_{y_{k+2}}^{y_{m}}\cdots \int_{y_{m+1}}^{\infty}\int_{y_{m+2}}^{\infty}\cdots \int_{y_{n-2}}^{\infty}n!\prod_{i=1}^{n-2}f(y_{i})(1-F(y_{n-1}))\\ \times \, dy_{n-2}\cdots dy_{m+2}\cdots \, dy_{k+2}\, dy_{1}\cdots dy_{m-1}\cdots \, dy_{k-1}\\ \end{split} \end{equation*} \begin{equation*} \boxed{ \begin{split} s=1-F(y_{n-1})\qquad ds=-f(y_{n-1})\, dy_{n-1}\\ \int_{y_{n-2}}^{\infty}n!\prod_{i=1}^{n-2}f(y_{i})(1-F(y_{n-1}))\times \, dy_{n-2}\\ =\int_{1-F(y_{n+2})}^{0}n!\prod_{i=1}^{n-3}f(y_{i})(-(s))\times ds=n!\prod_{i=1}^{n-3}f(y_{i})\Big[-\frac{s^{2}}{2}\Big]_{1-F(y_{n-2})}^{0}\\ =n!\prod_{i=1}^{n-3}f(y_{i})\frac{(1-F(y_{n-2}))^{2}}{2} \end{split} } \end{equation*} \begin{equation*} \begin{split} =\frac{n!}{2!} \int_{-\infty}^{y_{k}}\int_{-\infty}^{y_{k-2}}\cdots \int_{-\infty}^{y_{2}}\int_{y_{k+1}}^{y_{m}}\int_{y_{k+2}}^{y_{m}}\cdots \int_{y_{m+1}}^{\infty}\int_{y_{m+2}}^{\infty}\\ \cdots \int_{y_{n-2}}^{\infty}\prod_{i=1}^{n-3}f(y_{i})(1-F(y_{n-2}))^{2} \times \, dy_{n-2}\cdots dy_{m+2}\cdots \, dy_{k+2}\, dy_{1}\cdots dy_{m-1}\cdots \, dy_{k-1}\\ =\ldots=\\ =n! \int_{-\infty}^{y_{k}}\int_{-\infty}^{y_{k-2}}\\ \cdots \int_{-\infty}^{y_{2}}\int_{y_{k+1}}^{y_{m}}\int_{y_{k+2}}^{y_{m}}\prod_{i=1}^{m+1}f(y_{i})\frac{(1-F(y_{m+1}))^{n-m-1}}{(n-m-1)!}\times \, dy_{k+3}\, dy_{1}\cdots dy_{m-1}\cdots \, dy_{k-1}\\ =\frac{n!}{(n-m-1)!}(1-F(y_{m+1}))^{n-m-1}f(y_{m+1})f(y_{m})\cdots \int_{-\infty}^{y_{k}}\int_{-\infty}^{y_{k-2}}\\ \cdots \int_{-\infty}^{y_{2}}\int_{y_{k+1}}^{y_{m}}\int_{y_{k+2}}^{y_{m}}\cdots \int_{y_{m-1}}^{y_{m}} \prod_{i=1}^{m-1}f(y_{i})\times \, dy_{k+3}\, dy_{1}\cdots dy_{m-1}\cdots \, dy_{k-1}\\ =\frac{n!}{(n-m-1)!}(1-F(y_{m+1}))^{n-m-1}f(y_{m+1})f(y_{m})\cdots \int_{-\infty}^{y_{k}}\int_{-\infty}^{y_{k-2}}\\ \cdots \int_{-\infty}^{y_{2}}\int_{y_{k+1}}^{y_{m}}\int_{y_{k+2}}^{y_{m}}\cdots \int_{y_{m-1}}^{y_{m}} \prod_{i=1}^{m-1}f(y_{i})\times \, dy_{k+3}\, dy_{1}\cdots dy_{m-1}\cdots \, dy_{k-1}\\ =\frac{n!}{(n-m-1)!}(1-F(y_{m+1}))^{n-m-1}f(y_{m+1})f(y_{m}) \int_{-\infty}^{y_{k}}\int_{-\infty}^{y_{k-2}}\\ \cdots \int_{-\infty}^{y_{2}}(F(y_{m})-F(y_{k+1}))^{m-1-(k+1)}\frac{1}{(n-m-2)!}f(y_{k})f(y_{k+1})\Pi_{i=1}^{k-1}\\ =\frac{n!}{(n-m-1)!}\frac{1}{(n-m-2)!}(1-F(y_{m+1}))^{n-m-1}(F(y_{m})-F(y_{k+1}))^{m-k-2}\\ \times f(y_{m+1})f(y_{m})f(y_{k})f(y_{k+1})(F(y_{k}))^{k-1}\\ f_{X_{k},X_{k+1},X_{m},X_{m+1}}(y_{k},y_{k+1},y_{m},y_{m+1})=\frac{n!}{(n-m-1)!}\frac{1}{(n-m-2)!}(1-y_{m+1})^{n-m-1}\\ \times (y_{m}-y_{k+1})^{m-k-2}(y_{k})^{k-1}\cdot 1\cdot 1\cdot 1\cdot 1\\ U=\frac{X_{k}}{X_{k+1}}\qquad X_{k}=UZ\\ V=\frac{X_{m}}{X_{m+1}}\qquad X_{k+1}=Z\\ Z=X_{k+1} \qquad X_{m}=VQ\\ Q=X_{m+1}\qquad X_{m+1}=Q\\ |\mathbf{J}|= |\begin{bmatrix} \frac{\partial y_{k}}{\partial u}&\frac{\partial y_{k}}{\partial v}&\frac{\partial y_{k}}{\partial z}&\frac{\partial y_{k}}{\partial q}\\ \frac{\partial y_{k+1}}{\partial u}&\frac{\partial y_{k+1}}{\partial v}&\frac{\partial y_{k+1}}{\partial z}&\frac{\partial y_{k+1}}{\partial q}\\ \frac{\partial y_{m}}{\partial u}&\frac{\partial y_{m}}{\partial v}&\frac{\partial y_{m}}{\partial z}&\frac{\partial y_{m}}{\partial q}\\ \frac{\partial y_{m+1}}{\partial u}&\frac{\partial y_{m+1}}{\partial v}&\frac{\partial y_{m+1}}{\partial z}&\frac{\partial y_{m+1}}{\partial q} \end{bmatrix} |=|\begin{bmatrix} z&0&u&0\\ 0&0&1&0\\ 0&q&0&v\\ 0&0&0&1 \end{bmatrix}|\\ =|z\begin{bmatrix} 0&1&0\\ q&0&v\\ 0&0&1 \end{bmatrix}-0+u \begin{bmatrix} 0&0&0\\ 0&q&v\\ 0&0&1 \end{bmatrix}-0|\\ =|z(-(q\cdot 1\cdot 1))|=zq\\ \end{split} \end{equation*} \begin{equation*} \begin{split} f_{U,V,Z,Q}(u,v,z,q)=\frac{n!}{(n-m-1)!}\frac{1}{(n-m-2)!}(1-q)^{n-m-1}\\ \times (vq-z)^{m-k-2}(uz)^{k-1}\cdot zq\\ f_{U,V,Q}(u,v,q)=\frac{n!}{(n-m-1)!}\frac{1}{(n-m-2)!}(1-q)^{n-m-1}q\\ \times \int_{0}^{1}(vq-z)^{m-k-2}(uz)^{k-1}\cdot z\, dz \end{split} \end{equation*} At this step I am stuck, I have not fund a way to evaluate this integral. I want to find $f_{U,V}(u,v)$ and then the marginal distributions $f_{U}(u)$ and $f_{V}(v)$. Can it be done? Is this the best way to show independence between $U$ and $V$? Thanks in advance!

$\endgroup$
1
$\begingroup$

Rather than computing densities, you can work with moments: because the $X_{(k)}$ and the $V_j$ all take values in $(0,1)$, their joint moments fully determine their distributions. For example, it's easy to check that for a positive integer $p$, $$ \Bbb E[V_1^p]=2\int_{0<u<v<1}u^pv^{-p}\,du\,dv=2\int_0^1\int_0^v u^pv^{-p}\,du\,dv={1\over p+1}. $$ As these are also the moments of a random variable uniformly distributed on $(0,1)$, it follows that $V_1\sim U(0,1)$.

Now check that if $p_1,p_2, p_3$ are non-negative integers then $$ \Bbb E[X_{(1)}^{p_1}X_{(2)}^{p_2}X_{(3)}^{p_3}]=6\int_{u<v<w}u^{p_1}v^{p_2}w^{p_3}\,du\,dv\,dw={6\over(p_1+1)(p_1+p_2+2)(p_1+p_2+p_3+3)}. $$ From this it follows that for non-negative $q_1$ and $q_2$, $$ \Bbb E[V_1^{q_1}V_2^{q_2}]=\Bbb E[X_{(1)}^{q_1}X_{(2)}^{q_2-q_1}X_{(3)}^{-q_2}]={2\over (q_1+1)( q_2+2) }. $$ From this it follows that $V_1$ and $V_2$ are independent (the joint moments factor!) and that $V^2_2\sim U(0,1)$ (because $V_2^2$ has the correct moments!).

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.